Perforation of the Papilla of Vater in Wire-Guided Cannulation - Yuichi Takano; Masatsugu Nagahama; Eiichi Yamamura; Naotaka Maruoka; Hiroshi Takahashi (Canadian Journal of Gastroenterology and Hepatology)
Background. WGC in ERCP is considered a safe technique, although rare complications can occur. One unique complication of WGC is the perforation of the papilla of Vater by the guidewire. Subjects and Methods. Of 2032 patients who underwent ERCP at our department between January 2010 and December 2014, we selected 208 patients who underwent WGC for naïve papilla as subjects. A detailed examination of patients in whom a perforation occurred was conducted, and risk factors for perforations were investigated. Results. The perforation was observed in 7 of 208 patients (3.4%). All patients recovered with conservative treatment without the need for surgery. The perforation rate was significantly higher in the patients with juxtapapillary duodenal diverticula than those without diverticula (12.5% versus 0.6%, p<0.001). Cannulation of the bile duct was ultimately achieved in 5 of 7 patients; PSP was performed for 4 of these patients. Conclusion. Caution must be exercised when dealing with patients who have a juxtapapillary duodenal diverticula because they are at higher risk of perforations. Because these are small perforations made by a wire, most of them heal with conservative treatment. However, perforations can make cannulation difficult, and PSP may be useful for deep cannulation.